2012
DOI: 10.1161/hypertensionaha.111.188276
|View full text |Cite
|
Sign up to set email alerts
|

CD19 + CD5 + Cells as Indicators of Preeclampsia

Abstract: Abstract-Preeclampsia is a devastating pregnancy-associated disorder affecting 5% to 8% of pregnant women worldwide.It emerges as an autoimmune-driven disease, and, among others, the autoantibodies against angiotensin type 1 receptor II have been proposed to account for preeclampsia symptoms. Despite much attention focused on describing autoantibodies associated with preeclampsia, there is no clue concerning the cell population producing them. CD19 ϩ CD5 ϩ B-1a B cells constitute the main source of natural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 46 publications
2
62
2
1
Order By: Relevance
“…B cells can also be recruited by the chorioamniotic membranes [14] and constitute a portion of the choriodecidual leukocytes [16,57,58]. The role of B cells during pregnancy and its complications have been widely studied by Jensen and collaborators [59][60][61][62][63][64][65][66][67][68]. Taken together, these data provide further evidence that the adaptive limb of immunity is involved in the process of labor.…”
Section: Resultsmentioning
confidence: 79%
“…B cells can also be recruited by the chorioamniotic membranes [14] and constitute a portion of the choriodecidual leukocytes [16,57,58]. The role of B cells during pregnancy and its complications have been widely studied by Jensen and collaborators [59][60][61][62][63][64][65][66][67][68]. Taken together, these data provide further evidence that the adaptive limb of immunity is involved in the process of labor.…”
Section: Resultsmentioning
confidence: 79%
“…Even during pregnancy, B1a B cells producing natural antibodies are proposed to have detrimental effects on pregnancy outcome. We recently showed that the number of B1a B cells significantly decrease in the third trimester of normal pregnant women while remain elevated in pre-eclamptic patients (122). As patients suffering from pre-eclampsia have augmented serum hCG levels compared to normal pregnant women, we assumed that hCG may be responsible for the increased B1a B cell number.…”
Section: Hormonal Influence On Immune Cells During Pregnancymentioning
confidence: 99%
“…As patients suffering from pre-eclampsia have augmented serum hCG levels compared to normal pregnant women, we assumed that hCG may be responsible for the increased B1a B cell number. This assumption is further underlined by the fact that almost all B1a B cells express the LH/CG receptor and expand in vitro upon hCG stimulation (122). It was however shown that hCG inhibited antibody formation of murine B cells (123, 124).…”
Section: Hormonal Influence On Immune Cells During Pregnancymentioning
confidence: 99%
“…hCG, reported to be elevated in PE patients, was identified as one factor modulating the AT1-AA production by B1aB cells. 111 The application of an antibody that reduces the B-cell population could restore blood pressure and endothelin production in a rat model for PE. 112 …”
Section: The Final Players: B Cells Directing the Immune Response Tomentioning
confidence: 99%